2017
DOI: 10.18203/2320-1770.ijrcog20175862
|View full text |Cite
|
Sign up to set email alerts
|

A randomized comparative study of exteriorization of uterus versus in situ intra-peritoneal repair at cesarean delivery

Abstract: Background: Various caesarean delivery techniques have been compared in the past to assess the associated short-term and long-term advantages and disadvantages. Although uterine exteriorization at caesarean section is popular among obstetricians, safety of this technique remains a disputed matter. The aim of the present study was to compare the influence of uterine exteriorization or in situ repair on caesarean section morbidity.Methods: In this prospective, randomized, controlled study, 200 pregnant women wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…However, the difference did not reach a statistical significance ( p > 0.05). A similar result was found in many previous studies and in a recent meta-analysis, which concluded that there was no significant difference between these two uterine repair techniques for the length of hospital stay [ 17 , 21 , 37 , 44 , 47 ]. In terms of the length of hospital stay, it seems that there is neither a marked difference nor a strong association by using different uterine repair techniques.…”
Section: Surgical Techniques and Assistive Devices Used In Cesareasupporting
confidence: 89%
See 3 more Smart Citations
“…However, the difference did not reach a statistical significance ( p > 0.05). A similar result was found in many previous studies and in a recent meta-analysis, which concluded that there was no significant difference between these two uterine repair techniques for the length of hospital stay [ 17 , 21 , 37 , 44 , 47 ]. In terms of the length of hospital stay, it seems that there is neither a marked difference nor a strong association by using different uterine repair techniques.…”
Section: Surgical Techniques and Assistive Devices Used In Cesareasupporting
confidence: 89%
“…They concluded that shorter operating times also benefited from less blood loss and better accessibility while repairing the exteriorized uterus [34]. Moreover, in another study, a shorter time for uterine closure was found in the exteriorized uterine repair group than in the in situ group [47]. However, Doganay et al reported significantly shorter mean operative time in the in situ uterine repair group (36.8 vs. 44.6 min) than in the exteriorized uterine repair group in a large-scale randomized controlled trial, including 5002 women [36].…”
Section: Operative Timementioning
confidence: 96%
See 2 more Smart Citations